2016
DOI: 10.1002/anie.201606238
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Active Site Conformational Heterogeneity along the Trajectory of an Enzymatic Phosphoryl Transfer Reaction

Abstract: States along the phosphoryl transfer reaction catalyzed by the nucleoside monophosphate kinase UmpK were captured and changes in the conformational heterogeneity of conserved active site arginine side‐chains were quantified by NMR spin‐relaxation methods. In addition to apo and ligand‐bound UmpK, a transition state analog (TSA) complex was utilized to evaluate the extent to which active site conformational entropy contributes to the transition state free energy. The catalytically essential arginine side‐chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…Our ensemble data provided evidence against each model for KSI. Similarly, prior NMR data suggested that most of the substrate positioning needed to form a new bond occurs in forming the enzyme•substrate complex of the UMP/CMP kinase reaction (Zeymer et al, 2016). Future ensemble determinations with additional enzymes will test the generality of these conclusions.…”
Section: General Implicationsmentioning
confidence: 85%
“…Our ensemble data provided evidence against each model for KSI. Similarly, prior NMR data suggested that most of the substrate positioning needed to form a new bond occurs in forming the enzyme•substrate complex of the UMP/CMP kinase reaction (Zeymer et al, 2016). Future ensemble determinations with additional enzymes will test the generality of these conclusions.…”
Section: General Implicationsmentioning
confidence: 85%
“…Moreover, small changes in temperature and particularly in pH affect the rates substantially, thus generally allowing for a large range of arginine side‐chains to be characterised. It is envisaged that the new method serves as a particularly valuable tool to characterise active sites in enzymes,, protein‐protein or protein‐nucleic acid interactions, and phase separation, where arginine residues are expected to play a crucial role for biological function.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst a knowledge of protein backbone behaviour is often imperative to understand many aspects of protein functions, it is typically the side‐chains that directly mediate activity and participate in the important and functional interactions. Arginine residues are often crucial to many biological interaction interfaces because the flexible arginine side‐chain, consisting of a chain of aliphatic carbon atoms and a terminal guanidinium group, is capable of an array of hydrogen‐bonds and other interactions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein side chains have the ability to sample several conformations, which is important for many biological processes. Side-chain motions are often de-correlated from the backbone, [1][2][3] making it important to be able to specifically characterise them. The structure and conformational sampling of side chains are often derived from a combination of several NMR measurements, such as nuclear Overhauser effects (NOEs), three-bond scalar couplings, 4,5 residual dipolar couplings and spin-relaxation measurements.…”
mentioning
confidence: 99%